(3EOGQI GdCYeGd GdOhdjI (B:s (3GdEWGQ GdYGe (B/s - (3YHGS, Ydjs ((3GdbGgQI(B: s (3OGQ GdMGeO(B, s, 2003)
(3GdCYeGd GdOhdjI WHjYJgG(B-(3eLGdGJ JfXjegG,GdJLGQI GdOhdjI,GdfXQjGJ GdcdGSjcjI(B-(3GdhVY GdQGgf,efXeI GdJLGQI GdYGdejI heDSSGJgG,ejRGf GdeOahYGJ hCSYGQ UQa GdYedGJ,GdESJKeGQ GdCLfHj aj GdOhd GdfGejI(B-(3CfhGYg(B-(3fXQjGJg(B-(3SjGSGJg hETcGdjI GdJaGhV,GdEOGQI GdESJQGJjLjI aj T(B.(3e(B.(3M,GdJNWjW GdGSJQGJjLj aj T(B.(3e(B.(3L,JMdjd GdeNGWQ GdjSGSjI ddESJKeGQ GdCLfHj hGdHjFI GdbGfhfjI,GdHjFI GdeGdjI(B:(3GdCShGb GdeGdjI hGdfbOjI,GdHjFI GdeGdjI(B:(3GdeDSSGJ GdeGdjI GdOhdjI hGdBbdjejI,GdHjFI GdKbGajI hGdGLJeGYjI ddCYeGd GdOhdjI,JfejI GdehGQO GdHTQjI aj GdCYeGd GdOhdjI,ehVhYGJ NGUI aj GdJShjb GdOhdjs
(3HjHdjhZQGajG U(B.437s
Keywords: (3GOGQI GdGYeGds; (3GdJLGQI GdNGQLjIs